Preoperative physical activity and functional performance levels are predictors of acute postoperative outcomes in a private South African colorectal cancer cohort - Megan Whelan; Heleen van Aswegen; Ronel Roos; June Fabian; Brendan Bebington (AOSIS, 2021)
Background: For patients with colorectal cancer, surgical resection of the primary tumour remains the best treatment option. Surgery for colorectal cancer is being performed on patients who would previously not have been considered as suitable candidates. It remains to be seen which factors influence hospital length of stay (LOS) and the development of acute postoperative complications in South African patients. Objectives: The objectives of our study were to determine the modifiable factors that influence patients' development of postoperative complications and hospital LOS and, to identify the types of postoperative complications that develop. Method: A retrospective review and secondary analysis of information in an existing database of patients with colorectal cancer were conducted. Regression analysis statistics were used to determine the predictors of postoperative outcomes. The level of significance at which testing was performed was set at 5% (p ≤ 0.05). Results: Data of 125 patients were included. Surgical site infections and postoperative paralytic ileus were the most frequently reported postoperative complications. Preoperative vigorous-intensity physical activity (p = 0.048, β = -0.000) and functional performance status (p = 0.05, β = 0.926) significantly predicted hospital LOS and the incidence of postoperative complications, respectively. Conclusion: Preoperative physical activity and functional performance levels are predictors of acute postoperative outcomes in a private South African cohort of patients with colorectal cancer. Future research which includes other modifiable factors is required to make informed suggestions for changes in clinical practice. Clinical implications: Patients requiring surgery for colorectal cancer should be screened for signs of physical deconditioning and referred for physiotherapy intervention before elective surgery to optimise their recovery.